Effects of P2Y12 receptor inhibition with or without aspirin on hemostatic system activation: a randomized trial in healthy subjects - Traby, L.; Kollars, M.; Kaider, A.; Eichinger, S.; Wolzt, M.; Kyrle, P. A. (Journal of thrombosis and haemostasis, 2016)
Essentials In acute coronary syndromes, dual antiplatelet therapy inhibits platelets but confers a bleeding risk. Healthy male volunteers received clopidogrel or ticagrelor plus aspirin or clopidogrel or ticagrelor alone. The decrease in β‐thromboglobulin in shed blood was comparable after single and dual antiplatelet therapy. We hypothesize that patients with acute coronary syndromes may not require dual antiplatelet therapy. Summary Background Dual antiplatelet therapy with a P2Y12 inhibitor and aspirin is standard in acute coronary syndromes. Dual antiplatelet therapy causes more bleeding than single antiplatelet therapy with a P2Y12 inhibitor. Objectives To compare the effects of dual and single antiplatelet therapies on hemostatic system activation. Patients/Methods In a randomized, parallel‐group, double‐blind, placebo‐controlled study, 44 healthy volunteers received clopidogrel (600 mg, then 150 mg d–1) and aspirin (100 mg d–1) or placebo for 7 days; An additional 44 volunteers received single‐dose ticagrelor (180 mg) and aspirin (300 mg) or placebo. β‐Thromboglobulin (β‐TG [IU L–1]) and prothrombin fragment 1.2 (f1.2 [nmol L–1]) were measured in blood obtained from bleeding time incisions. Data are given as geometric mean ratio (GMR [95% confidence interval]) to describe the differences in the first 2 h and as mean differences (Δ [95% confidence interval]) in area under the curve (AUC) to discriminate differences in effects over the total observation time. Results Clopidogrel plus aspirin and clopidogrel plus placebo reduced β‐TG by a GMR of 0.51 (0.42–0.63) and 0.54 (0.46–0.64) at 2 h. Ticagrelor plus aspirin and ticagrelor plus placebo decreased β‐TG by a GMR of 0.38 (0.26–0.57) and 0.47 (0.31–0.72). Ticagrelor plus aspirin and ticagrelor plus placebo reduced f1.2 by a GMR of 0.58 (0.45–0.75) and 0.55 (0.38–0.80); clopidogrel did not. Over 24 h, no difference in β‐TG occurred between clopidogrel plus aspirin and clopidogrel plus placebo (ΔAUC = −2.9 [−9.9 to 4.1]) or between ticagrelor plus aspirin and ticagrelor plus placebo (ΔAUC = −3.5 [−11.8 to 4.7]). No difference in f1.2 occurred between clopidogrel plus aspirin and clopidogrel plus placebo (ΔAUC = −4.2 [−10.2 to 1.8]) or between ticagrelor plus aspirin and ticagrelor plus placebo (ΔAUC = −3.6 [−10.9 to 3.7]). Conclusions P2Y12 inhibitor monotherapy and dual antiplatelet therapy inhibit hemostatic system activation to a comparable extent.